(untitled) (VERUM: Journal of Scientific Initiation, 2024)
This article analyzes the data related to the progress and fulfillment of the goal 6 of the National Education Plan - PNE (2014-2024), which refers to full-time education, for the city of São João da Boa Vista in the state of São Paulo, Brazil, using as methodological procedures: bibliographical review, documentary analysis and quantitative data. The findings revealed that the before mentioned municipality has reached the goal 6 proposed by PNE quantitatively. However, efforts must be made to ensure the achievement of the goal also from the qualitative point of view, indicating the need for other studies on the topic.